Disseminated American Cutaneous Leishmaniasis in a patient with AIDS - Coura, José Rodrigues (1987)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Departamento de Medicina Tropical. Rio de Janeiro, RJ, Brasil.